Analisis Penggunaan Aplikasi BJB DIGI Mobile Banking dengan Menggunakan Pendekatan Technology Acceptance Model (TAM) - Andi Zhillan Sabtina Syawali; Anggi Syahadat Harahap; Hafid Aditya Pradesa; Fikri Aditya Tri Andikaputra (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Bank BJB is one of the BUMD banks that has developed a mobile banking application system called BJB DIGI where the application can make it easier for Bank BJB customers to carry out financial transactions. However, in the development of this application there are still many deficiencies and the level of doubt of Bank BJB customers to use the application is still high. Therefore, a study was conducted to determine the level of acceptance of the BJB DIGI application at Bank BJB Soreang Branch Office using the TAM theory. This research was conducted using 175 samples who were BJB DIGI users using the snowball sampling technique. The results of this study explain that of the four variables that have the highest average value, there is the intention variable to use BJB DIGI. In addition, the results found that the level of ease of use and usability of BJB DIGI has a significant influence on the intention to use BJB DIGI. Meanwhile, the intention variable to use BJB DIGI was found to have a significant influence on the level of use of BJB DIGI. However, on the other hand, the variable level of ease of use and usability of BJB DIGI was found to have no significant effect on the level of use of BJB DIGI at Bank BJB Soreang Branch Office. Discussion of important research findings is presented in the discussion section of this research.